Hubungan Emotional Intelligence Terhadap Kinerja Perawat Wanita di Instalasi Rawat Inap RSUD Dr. Pirngadi - Romauli Siallagan; Rispalina Ritonga (Yayasan Literasi Sains Indonesia, 2022)
Nursing staff is an important component in the form of health services in hospitals. The number of female workers tends to work in the social work and health sectors. The performance of nurses in RSUD Dr. Pirngadi Medan City is low. This study aims to analyze the effect of emotional intelligence on female nurses in inpatient installations at RSUD Dr. Pirngadi Medan City, the population in this study were all inpatient nurses at RSUD Dr. Pirngadi Medan City as many as 191 nurses consisting of 14 rooms with a sample of 115 nurses. This study uses an analytical survey with a cross sectional approach which aims to determine how closely the relationship between variables. The data management technique was carried out by means of univariate, bivariate and multivariate analysis using multiple logistic regression tests. The results showed that nurses at RSUD Dr. Pirngadi Medan City with variables with emotional intelligence variables on the performance of implementing nurses at RSUD Dr. Pirngadi Medan City with an OR regression coefficient of 3.797. Suggestions for health services are expected to pay attention to the right policies to be implemented in hospitals related to the welfare of nurses, organize ESQ training activities that aim to further increase emotional intelligence and provide rewards for the performance achieved.